Design and Calculation of Hydraulic Transmission System of Loader. (November 2020) - Jing, Zhou; Qi, Han
Abstract: In order to give full play to the power of the engine, it is necessary to find the operating point of the engine and the hydraulic torque converter working together. This paper designs the hydraulic shift system of ZL50 loader with advanced mechanism theory. Firstly, the hydraulic variable speed system of the loader is designed according to the speed and maximum traction of the loader. Then, by calculating the traction characteristics of the loader and the heating of the drive system and evaluating its performance, it provides a reliable theoretical basis for the overall design of the loader.